PLOD1 promotes the malignancy of hepatocellular carcinoma by facilitating the NF-κB/IL-6/STAT3-dependent TCA cycle - Chengfei Zhang; Yangchun Zhou; Minghua Hu; Yue Pan; Xin Chen; Qi Sun; Zhijie Ma; Cheng Wang; Yong Zha; Feng Zhu; Hongping Xia (JHEP Reports)
Background & Aims: Procollagen lysyl hydroxylase 1 (PLOD1) is crucial in regulating collagen synthesis and cross-linking. However, its roles and underlying mechanisms in the progression of hepatocellular carcinoma (HCC) remain unclear. Herein, we aimed to investigate the underlying biological functions and mechanisms of PLOD1 in HCC. Methods: The expression levels of PLOD1 in HCC were measured by qPCR, Western blot, and immunohistochemistry. Cell proliferation, apoptosis, and stemness were examined by CCK8, flow cytometry, sphere formation, and aldehyde dehydrogenase activity assays. The subcutaneous tumorigenicity model, orthotopic tumorigenicity model, and hepatotoxin-induced HCC model were used for in vivo experiments. RNA-sequence and untargeted metabolomics analysis were performed to identify underlying mechanisms. Results: PLOD1 is found to be highly expressed in both human (p <0.0001) and mouse HCC (p <0.01) and is associated with a poor prognosis (p = 0.047). In vitro and in vivo experiments reveal that overexpression of PLOD1 promotes the proliferation and stemness of HCC cells. Meanwhile, the depletion of PLOD1 attenuates the occurrence and growth of HCC, leading to cell cycle arrest (p <0.01) and apoptosis (p <0.001) in HCC. Mechanistically, PLOD1 positively regulates the NF-κB/IL-6/STAT3 signaling pathway and accelerates TCA cycle metabolic reprogramming. Blocking the NF-κB/IL-6/STAT3 signaling pathway and TCA cycle can effectively mitigate PLOD1-induced proliferation and stemness of HCC cells. Conclusions: Our study uncovers the PLOD1/NF-κB/IL-6/STAT3 axis as a therapeutic target for inhibiting the progression and stemness of HCC. Impact and implications: The roles and underlying mechanisms of PLOD1 in the progression of HCC remain unclear. In this study, we report that PLOD1 is highly expressed in patients with HCC and promotes the proliferation and stemness of HCC cells by activating the NF-κB/IL-6/STAT3-dependent TCA cycle. Knocking down hepatic PLOD1 using adeno-associated virus results in reduced progression of HCC in mice, suggesting that PLOD1 may serve as a potential therapeutic target for HCC.